Analysis Of Factors Related To Anxiety Level In Postpartum Mothers at Citra Insani Maternity Home, Semarang - Yulvira Febriani; Rasipin Rasipin; Runjati Runjati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The cause of postpartum anxiety is still unknown. Many adverse developmental effects after anxiety can be caused to the mother, baby, and her family. The research aims to analyze factors related to postpartum anxiety level at Citra Insani Maternity Home, Semarang. This study used an analytic observational research design with a cross sectional approach. Sampling was conducted at the Citra Insani Maternity Hospital in Semarang City from February to March 2020 using purposive sampling. The study subjects are 40 postpartum mothers in the second day. The instrument used was a Postpartum Specific Anxiety Scale questionnaire. The factors studied were age, parity, education, employment status, and history of anemia. Data analysis was performed using the Chi-square test. The results is the majority of mothers experienced moderate anxiety (60%). Based on data analysis, there is no significant relationship between age, parity, education, employment status and history of anemia with postpartum anxiety levels